1991
DOI: 10.2307/3676540
|View full text |Cite
|
Sign up to set email alerts
|

Postfledging Dispersal, Habitat Imprinting, and Philopatry in a Montane, Migratory Sparrow

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(46 citation statements)
references
References 19 publications
3
43
0
Order By: Relevance
“…Why do they move long distances towards the north from their breeding sites prior to a southerly migration? It has been suggested that before migration young migratory birds disperse to find favourable areas (living space, food and shelter; Morton et al 1991, Baker 1993. They may therefore avoid competition with adults, enhance survival and improve body condition in preparation for migration (Morton et al 1991, Baker 1993.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Why do they move long distances towards the north from their breeding sites prior to a southerly migration? It has been suggested that before migration young migratory birds disperse to find favourable areas (living space, food and shelter; Morton et al 1991, Baker 1993. They may therefore avoid competition with adults, enhance survival and improve body condition in preparation for migration (Morton et al 1991, Baker 1993.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that before migration young migratory birds disperse to find favourable areas (living space, food and shelter; Morton et al 1991, Baker 1993. They may therefore avoid competition with adults, enhance survival and improve body condition in preparation for migration (Morton et al 1991, Baker 1993. Ultimate factors could be to collect information to identify a future breeding site (hereafter IBS hypothesis) or create a navigational target or a mental map (hereafter CNT hypothesis) to return the following spring (Morton et al 1991;Baker 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Don~izar and F. Hiraldo, unpublished data). If kestrels, like other raptors (Cade & Bird, 1990;Cade & Jones, 1993) and, in general, other birds (Klopfer & Ganzhorn, 1985;Morton et al, 1991), have an imprinted image of the habitat in which they were born it could be expected that individuals will tend to breed in urban areas even if the quality of the surrounding foraging habitats has declined. It would be interesting to find out if adequate foraging habitat is present far from villages and if these areas are not colonized because of low availability of adequate nesting sites.…”
Section: Discussionmentioning
confidence: 99%